The economic impact of telecommunications diffusion on UK productivity growth - Lisa Correa (Queen Mary University of London, Department of Economics, 2003)
This paper investigates the relationship between telecommunications infrastructure competition, investment and productivity. Using econometric modelling and input-output economics, the analysis examines and measures the extent to which telecommunications has contributed to national and sectoral productivity performance. The main findings from this paper suggests that most industries have benefited from the incorporation of advances of telecommunications technology, which might have, amongst other things, emanated from encouraging infrastructure investment, in their production processes. Thus the analysis demonstrates that U.K. government policies on telecommunications and its investment incentives may have wide-reaching consequences for not only the telecommunications industry but also the economy as a whole.
Keywords: D24; D57; L96; O30; O40; O47; 330; Productivity; Input-output analysis; Technical change; Telecommunications; Telekommunikationsinfrastruktur; Wettbewerb; Investition; Wirkungsanalyse; Input-Output; Produktivit\~AƒÂt; Wirtschaftswachstum; Sch\~AƒÂtzung; Gro\~AƒÅbritannien